2011
DOI: 10.1073/pnas.1015287108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for ubiquitin and ISG15 cross-reactivity in viral ovarian tumor domains

Abstract: Crimean Congo hemorrhagic fever virus (CCHFV) is a deadly human pathogen that evades innate immune responses by efficiently interfering with antiviral signaling pathways mediated by NF-κB, IRF3, and IFNα/β. These pathways rely on protein ubiquitination for their activation, and one outcome is the modification of proteins with the ubiquitin (Ub)-like modifier interferon-stimulated gene (ISG)15. CCHFV and related viruses encode a deubiquitinase (DUB) of the ovarian tumor (OTU) family, which unlike eukaryotic OTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(185 citation statements)
references
References 29 publications
8
177
0
Order By: Relevance
“…The ovarian tumor (OTU) domain proteases encoded by nairoviruses and arteriviruses help counteract both ubiquitylation and ISGylation by cleaving ubiquitin and ISG15 from target proteins (24). Structural studies showed that the ovarian tumor protease binds to the ubiquitin and C-terminal UBL domain of ISG15 (25,26). Previous biochemical study and the ISG15-NS1B complex structure shown here reveal that NS1B just targets the N-terminal UBL domain and the linker of ISG15 (9).…”
Section: Resultsmentioning
confidence: 99%
“…The ovarian tumor (OTU) domain proteases encoded by nairoviruses and arteriviruses help counteract both ubiquitylation and ISGylation by cleaving ubiquitin and ISG15 from target proteins (24). Structural studies showed that the ovarian tumor protease binds to the ubiquitin and C-terminal UBL domain of ISG15 (25,26). Previous biochemical study and the ISG15-NS1B complex structure shown here reveal that NS1B just targets the N-terminal UBL domain and the linker of ISG15 (9).…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, ISG15 has been shown to conjugate to proteins in a manner similar to ubiquitin (40,41). Modifications and interference of antiviral signaling pathways involving ISG15 are mechanisms used by Crimean-Congo hemorrhagic fever virus, a bunyavirus, to evade the innate immune response (40). Upregulation of numerous ISG genes, including ISG15, and continuous stimulation of the innate antiviral response have been demonstrated in blood and tissues of bovine fetuses and cattle infected with BVDV (28,39).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the Mx protein, ISG15 is induced by type I IFN and has been associated with antiviral activity (29). In recent studies, ISG15 has been shown to conjugate to proteins in a manner similar to ubiquitin (40,41). Modifications and interference of antiviral signaling pathways involving ISG15 are mechanisms used by Crimean-Congo hemorrhagic fever virus, a bunyavirus, to evade the innate immune response (40).…”
Section: Discussionmentioning
confidence: 99%
“…The tick-borne properties of the nairoviruses, and the large L segment existing in their genome make them different from other members of the Bunyaviridae viruses [1,2]. Crimean-Congo Hemorrhagic Fever (CCHF) constitutes a public health treat due to its high mortality rate in hospitalized patients [1][2][3][4][5][6][7][8][9][10]. It has been first reported in both the Crimea and Congo, since then there have been outbreaks in different parts of the world including Africa, Asia, and Eastern Europe [5,9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%